Examining the Interactive Endogeneity Relationship between R&D Investment and Financially Sustainable Performance: Comparison from Different Types of Energy Enterprises - Kalon Si (Energies, 2020)
This paper employs the cluster analysis to classify the energy sector into three types, namely, technology-, capital-, and labor-intensive energy company. It then studies the interactive endogenous relationship between R&D investment and financially sustainable performance and the moderate effect of the executive incentive through three-stage least squares (3SLS) of the simultaneous equations model (SEM). The results show that for the technology-intensive energy company, an increase in the previous period in R&D investment improves the current period of financially sustainable performance, and the improvement in the current period in financially sustainable performance results in a decline in financially sustainable performance in the next period, which demands an increase in R&D investment subsequently. In contrast, for the capital-intensive energy company, R&D investment can significantly improve the financially sustainable performance in the current period, and the improvement in financially sustainable performance can also promote the intensity of next period R&D investment. For the labor-intensive energy company, R&D investment depends on the company’s previous period returns, while R&D investment has no significant impact on the financially sustainable performance in the current period and the next period. In addition, the salary incentives for executives have a significant positive moderate effect on the relationship between R&D investment and financially sustainable performance, especially in the technology-intensive energy company, while equity incentives for executives do not show any significant effect in the sample for different types of companies.